2015
DOI: 10.1039/c5cc00039d
|View full text |Cite
|
Sign up to set email alerts
|

Water-soluble dopamine-based polymers for photoacoustic imaging

Abstract: Here we present a facile synthetic method yielding a linear form of polydopamine via Kumada-coupling, which can be converted into water-soluble melanin, generating high contrast in photoacoustic imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 31 publications
(40 reference statements)
1
41
0
1
Order By: Relevance
“…The PA signals were again overlaid on the US images. An exponential decline in the PA signal intensity with the increase of injection depth (d, mm) was observed, which is in accordance with the previously published data from Repenko et al 36 The ICG liposome signal was clearly resolved till the depth of 10 mm, which is the relevant depth for subcutaneous tumor xenografts in mice. 37 Such a signal depth is also appropriate for several clinical applications such as monitoring of drug delivery to superficial skin tumors 38 as well as endoscopic detection of gastrointestinal tumors, 8 but certainly is not the limit that can be achieved in vivo.…”
Section: Phantom Experimentssupporting
confidence: 92%
See 1 more Smart Citation
“…The PA signals were again overlaid on the US images. An exponential decline in the PA signal intensity with the increase of injection depth (d, mm) was observed, which is in accordance with the previously published data from Repenko et al 36 The ICG liposome signal was clearly resolved till the depth of 10 mm, which is the relevant depth for subcutaneous tumor xenografts in mice. 37 Such a signal depth is also appropriate for several clinical applications such as monitoring of drug delivery to superficial skin tumors 38 as well as endoscopic detection of gastrointestinal tumors, 8 but certainly is not the limit that can be achieved in vivo.…”
Section: Phantom Experimentssupporting
confidence: 92%
“…36 The Vevo LAZR system features peak energies of 45±5 mJ, with a pulse duration of 4-6 ns at adjustable wavelengths between 680 and 970 nm (2 nm step size). In combination with the PA signal, high-resolution US images were acquired at 21 MHz (central frequency).…”
Section: Pa Imagingmentioning
confidence: 99%
“…However, materials intended for biomedical applications must be biocompatible. Although both FND and PDA are highly biocompatible materials, [8c,15h] we evaluated the biocompatibility of FND and PEGylated FND@PDA as a function of the concentration and incubation time using the (2-(4-Iodophenyl)-3-(4-nitrophenyl)-5-(2,4-disulfophenyl)-2H-tetrazolium sodium salt (WST-1) cell viability assay with mouse bone marrow-derived dendritic cells (BMDCs) and HeLa cells. Dendritic cells are antigen presenting cells that capture, process, and present antigens, and trigger T-cell mediated immune responses.…”
Section: Resultsmentioning
confidence: 99%
“…[14] PDA, which is a major pigment in naturally occurring eumelanin, has attracted attention due to its properties including adhesion, free radical quenching, metal ion chelation, large photoacoustic cross-section, and biocompatibility. [15] In addition, the presence of catechol/quinone groups on the PDA shell permits further reactions with amine or thiol containing molecules via Schiff base formation or Michael addition, respectively. The PDA encapsulation approach therefore provides a versatile platform for surface modification with a variety of functional molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Repenko et al have reported a synthesis method for linear polydopamine via Kumada coupling. The obtained product can be converted into water‐soluble melanin, showing a promising potential for photoacoustic imaging . In this synthesis, dopamine is first brominated to p ‐dibrominated dopamine; then functional hydroxyl and amine groups in p ‐dibrominated dopamine are protected using t Boc.…”
Section: The Modulation Of Melanin‐like Materialsmentioning
confidence: 99%